Translanguaging in Pedagogy: A Case Study of Chinese Students’ Meaning-Making in an English-Medium Indonesian University - Puji Lestari; Anggi Purwa Lestarina; Alya Ditha Berliana; Inpresta Natalia; Ahmad Najib Mutawally (Universitas Islam Negeri Palopo, 2025)
This study explores how translanguaging shapes academic learning and everyday interactions among Chinese students in an English-medium instruction (EMI) context at President University in Indonesia. While English functions as the primary language of instruction, students frequently navigate Mandarin as their first language and Bahasa Indonesia for daily communication, creating a dynamic multilingual environment. Grounded in García’s translanguaging framework, this qualitative descriptive case study investigates how students mobilize their linguistic repertoires to support academic comprehension, emotional expression, social participation, and identity negotiation. Data were collected through multilingual reflective journals written by 30 Chinese undergraduate students over a six-week period, with three representative reflections presented in Mandarin, English, and Bahasa Indonesia. Content analysis indicates that translanguaging operates as a crucial pedagogical and social resource, enhancing comprehension, emotional expression, social interaction, and identity negotiation. By foregrounding students’ reflective accounts, this study contributes to the limited body of research on translanguaging in Indonesian EMI higher education and provides empirical insight into multilingual meaning-making from learners’ perspectives. The findings highlight the importance of linguistically flexible pedagogies and suggest that EMI institutions should recognize translanguaging as a valuable resource for supporting multilingual students’ academic engagement.